Characteristics of Shoes with Musculoskeletal Complaints on Foot and Ankle of Sales Promotion Girl - Amaliyah, Mas; Indrayani, Reny; Ma’rufi, Isa (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Musculoskeletal complaints are a series of aches in the tendons, muscles, and nerves due to activities with high repetition rates resulting in tissue damage and pain in the muscles. Musculoskeletal complaints are experienced by many female workers due to work demands. Job demands such as the obligation to use high heels when working. Jobs related to the use of high heels are sales promotion girl (SPG). This study uses a quantitative approach. This type of research is observational analytic with cross sectional design. The assessment of musculoskeletal complaints in this study used the Foot and Ankle Outcomes Score (FAOS) questionnaire. Based on the results of the Spearman test factors associated with musculoskeletal complaints on feet and ankles of SPG at Golden Market Jember include individual factors consisting of length of work (ÃÂ = 0,000; r = 0.617; negative direction), BMI (ÃÂ = 0.022; r = 0.314; unidirectional), and sports habits (ÃÂ = 0.045; r = 0.617, opposite). The work factor is static position (ÃÂ = 0,000; r = 0.530; opposite). Shoe characteristic variables consist of shoes type (ÃÂ = 0.022; r = 0.313, opposite), duration of use (ÃÂ = 0,000; r = 0.547; direction), high heels (ÃÂ = 0,000; r = 0.855; direction), and suitability shoe size (ÃÂ = 0,000; r = 0.584; unidirectional). Factors not related to musculoskeletal complaints on the feet and ankles are age (ÃÂ = 0.027; r = 0.850; unidirectional).